2008
DOI: 10.1002/pd.1899
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy after preimplantation genetic diagnosis for carrier of t(2;7)(p11.2;q22) with high rates of unbalanced sperm and embryos: a case report

Abstract: Background Regarding the literature on the results of preimplantation genetic diagnosis (PGD) in reciprocal chromosomal translocation carriers seems to prevail a view that this method reduces the frequency of miscarriages, and the pregnancy rate is directly proportional to the number of normal spermatozoa. Therefore, we compared the results of sperm karyotype analysis of a carrier of familial t(2;7)(p11.2;q22) with PGD results. The carrier was ascertained as his wife had had two miscarriages.Methods Empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
3
13
0
1
Order By: Relevance
“…We did not observe that Robertsonian translocation t(13;17) affects the global nuclear architecture of the pig sperm nucleus (either looking at centromeres, telomeres or gonosomes). The effect of translocations on gonosomes topology described in Wiland et al 2008 [29] may be due to the important rate of unbalanced gametes in sperm from the analyzed infertile patients [54], [55]. We observed a strong impact of the Robertsonian translocation on SSC13 position within the nucleus.…”
Section: Discussionsupporting
confidence: 57%
“…We did not observe that Robertsonian translocation t(13;17) affects the global nuclear architecture of the pig sperm nucleus (either looking at centromeres, telomeres or gonosomes). The effect of translocations on gonosomes topology described in Wiland et al 2008 [29] may be due to the important rate of unbalanced gametes in sperm from the analyzed infertile patients [54], [55]. We observed a strong impact of the Robertsonian translocation on SSC13 position within the nucleus.…”
Section: Discussionsupporting
confidence: 57%
“…Sperm cells from all carriers were able to fertilize in vivo. The case of T3 was earlier described by Midro et al (2006); T2 was described by Wiland et al (2008), T4 was described by Midro et al (personal communication). For our analysis chromosomes 7, 9, X, and Y were chosen.…”
Section: Semen Collection and Preparationmentioning
confidence: 92%
“…Scriven et al (2013) reported that PGD can reduce the risk of miscarriage to the level found in the general population, and that PGD benefits couples with high-risk translocations. Other studies have reported successful birth after PGD for couples carrying an identical balanced reciprocal translocation (Wiland et al, 2008;Mackie et al, 2010;Beyazyurek et al, 2010). However, there are also risks associated with assisted reproduction treatment.…”
Section: Discussionmentioning
confidence: 99%